Factors Influencing Brand Equity of Bali as a Tourism Destination - Surya Diarta, I Ketut; Pitana, I Gde; Darma Putra, Nyoman; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 2 Number 2 (September 2015)DO - 10.24922/eot.v2i2.19501)
Globally, competition among tourism destinations is more stringent in getting foreign tourists, including Bali. One effort to win the competition is increasing destination brand equity through maintaining its influencing factors and gaining tourist positive behavior toward destination. This effort, in long run, will increase and stabilize destination revenue and sustainability. This research aims to analyze factors influencing brand equity of Bali as a tourism destination. This research was conducted in Bali’s five major tourism objects. The 240 foreign tourists were chosen as respondents through convenience sampling technique. Data were analyzed using factor analysis. The results showed that factors that significantly influenced Bali brand equity were: symbolic and experiential benefit factor, direct and indirect destinations attributes, destination reliability and tangibility, assurance and empathy, brand destinations recognition and recall, destinations common psychological attributes, destination common functional attributes, unique functional attributes, behavioral loyalty, destination awareness, and attitudinal loyalty. Given the fluctuative nature of brand equity, Bali needs a consistent effort to maintain or to enhance brand equity of Bali as a tourism destination. Maintaining the dominant factors that influence the strength of brand equity can be used as a basis to develop destination branding strategy to expand market segment,  choose the right target market, and anchoring destination position in world market competition.
Keywords: brand, equity, Bali, tourism, destination